Pemodelan dan Verifikasi Aliran Dua Fase (Air-Udara) di Belokan 90Â° - Nugraha, Arif Yunizar; Soenoko, Rudy; Wahyudi, Slamet (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
Two phase flow in a piping installation is influenced by the interaction between phases, geometry and orientation (vertical or horizontal), flow direction (up or down) that may affect the flow pattern. In contrast to single phase flow which only influenced by the Reynolds number in the formula of density, viscosity and pipe diameter. So the two phase flow has an interesting phenomenon to be studied which is the result of the pressure drop to form a flow pattern. The purpose of this study are to determine the pressure drop that occurs in the 90Â° from the horizontal position to a vertical position, and to analyze the flow pattern of two-phase fluid (water-air) at 90Â° in computational simulation and visualization verified with the help of high-speed digital camera. This study used clear PVC pipe (CPVC) and acrylic (PMMA) material in the 90Â° curves–test section with the aim to observe the flow pattern visualization then analyzed through simulation modeling with ANSYS software and verified experimentally. The calculation of the pressure drop in the 90Â° curve calculated theoretically and experimentally so that research can be studied scientifically. There was relationship between the flow patterns of the amount of pressure drop in the two-phase flow curves 90Â° of the thickness of the interface. The bigger the thickness of the interface, the pressure drop decreases both theoretically and experimentally due to the friction between the interfaces associated with friction factor, in this case is influenced by the Reynolds number and its value is inversed so the greater proportion of the air volumetric (Î²) then the Reynolds water number (Re SL) will decrease and increases friction between phase, besides the back pressure in the curve also affect the thickness 90Â° interface.There is wavy flow or turbulence in the bottom of horizontal pipe when the flow is laminar, it because of gravitation and centrifugal force or twin eddy in the actual speed ratio ( ð‘£ ðº ð‘£ ð¿) . The conditions influenced the flow pattern and pressure drop. The highest value of speed ratio ( ð‘£ ðº /ð‘£ ð¿ ) is 1,824 at vSG 0,076 m/s and the lowest is 0,423 at v SG 0,025 m/s.Keywords: two phase flow; pressure drop; flow pattern and curves